Videografia - Soares, Ismar de Oliveira; Magno, Maria Ignês Carlos (Comunicação & Educação, 1996)
A video selection on social movements in Brazil, on the late 19th Century and early 20th. Issues like Canudos, Contestado war, Old Republic.